Low-Power Inversion Recovery MRI Preserves Brain Tissue Contrast for Patients with Parkinson Disease with Deep Brain Stimulators - Sarkar, S.N.; Papavassiliou, E.; Rojas, R.; Teich, D.L.; Hackney, D.B.; Bhadelia, R.A.; Stormann, J.; Alterman, R.L. (American Journal of Neuroradiology, 2014)
BACKGROUND AND PURPOSE: Fast spin-echo short τ inversion recovery sequences have been very useful for MR imaging–guided deep brain stimulation procedures in Parkinson disease. However, high-quality fast spin-echo imaging deposits significant heat, exceeding FDA-approved limits when patients already have undergone deep brain stimulation and need a second one or a routine brain MR imaging for neurologic indications. We have developed a STIR sequence with an ultra-low specific absorption rate that meets hardware limitations and produces adequate tissue contrast in cortical and subcortical brain tissues for deep brain stimulation recipients. MATERIALS AND METHODS: Thirteen patients with medically refractory Parkinson disease who qualified for deep brain stimulation were imaged at 1.5T with a fast spin-echo short τ inversion recovery sequence modified to meet conditional MR imaging hardware and specific absorption rate restrictions. Tissue contrast-to-noise ratios and implant localization were objectively and subjectively compared by 2 neuroradiologists, and image quality for surgical planning was assessed by a neurosurgeon for high and low specific absorption rate images. RESULTS: The mean contrast-to-noise ratio for cerebral tissues without including the contrast-to-noise ratio for ventricular fluid was 35 and 31 for high and low specific absorption rate images. Subjective ratings for low specific absorption rate tissue contrast in 77% of patients were identical to (and in a few cases higher than) those of high specific absorption rate contrast, while the neurosurgical coordinates for fusing the stereotactic atlas with low specific absorption rate MR imaging were equivalent to those of the high specific absorption rate for 69% of patients. CONCLUSIONS: Patients with Parkinson disease who have already had a deep brain stimulation face a risk of neural injury if routine, high specific absorption rate MR imaging is performed. Our modified fast spin-echo short τ inversion recovery sequence conforms to very conservative radiofrequency safety limits, while it maintains high tissue contrast for presurgical planning, postsurgical assessment, and radiologic evaluations with greater confidence for radiofrequency safety. CNRcontrast-to-noise ratioDBSdeep brain stimulator or stimulationFSTIRfast spin-echo short τ inversion recoverySARspecific absorption ratePDParkinson diseaseRFradiofrequencySTNsubthalamic nucleus